Phenotypic plasticity of Monilinia spp. in response to light wavelengths: From in vitro development to virulence on nectarines - Verde-Yáñez, Lucía; Vall-llaura, Núria; Usall, Josep; Teixidó, Neus; Torres, Rosario (International journal of food microbiology, 2022)
The development of brown rot in stone fruit caused by the necrotrophic fungus Monilinia spp. is influenced by many abiotic factors, such as temperature, humidity, and light. Specifically, filamentous fungi perceive light as a signal for ecophysiological and adaptive responses. We have explored how specific light wavelengths affect the in vitro development, the regulation of putative development genes and the virulence of the main species of Monilinia (M. laxa, M. fructicola and M. fructigena). After subjecting Monilinia spp. to different light wavelengths (white, black, blue, red, far-red) for 7 days, several differences in their phenotype were observed among light conditions, but also among species. These species of Monilinia exhibited a different phenotypic plasticity in response to light regarding pigmentation, growth, and specially conidiation of colonies. In this sense, we observed that the conidial production was higher in M. laxa than M. fructicola, while M. fructigena showed an inability to produce conidia under the tested conditions. Growth rate among species was significantly lower in M. fructicola under red light wavelength while among light conditions it was increased under far-red light wavelength for M. laxa and under black light for M. fructicola; in contrast, no statistical differences were observed for M. fructigena. Gene expression analysis of 13 genes involved in fungal development of Monilinia spp. revealed a significant difference among the three species of Monilinia, and especially depended on light wavelengths. Among them, a high expression of OPT1, RGS2, RGS3 and SPP1 genes was observed in M. laxa, and LTF1 and STE12 in M. fructicola under black light. In contrast, a high expression of REG1 and C6TF1 genes occurred in both M. fructicola and M. laxa subject to red and far-red light wavelength, respectively. When nectarines were artificially infected with M. laxa and M. fructicola subjected to black light, the virulence was clearly reduced, but not in M. fructigena. Overall, results presented herein demonstrate that light wavelengths are a key abiotic factor for the biology of Monilinia spp., specially modulating its capacity to form conidia, and thus, influencing its spreading and the onset of the disease on nectarines during postharvest. •M. laxa and M. fructicola present a similar behaviour, but not M. fructigena.•The conidial production is higher in blue light for M. laxa and M. fructicola.•M. fructicola growth rate is reduced under red light compared to the other species.•Virulence in nectarines decreases in M. laxa and M. fructicola under black light.•M. fructigena reveals a similar behaviour among darkness and light wavelengths.